The use of HIV-1 integration site analysis information in clinical studies aiming at HIV cure - Maja Kiselinova; Ward De Spiegelaere; Linos Vandekerckhove (Elsevier, 2016)
The mechanisms for the establishment and the persistence of the latent HIV-1 reservoir remain to be completely defined. HIV-1 infection is characterised by the integration of the reverse transcribed proviral DNA into the host's genome. This integrated proviral DNA can remain replication silent, but a small part of it is fully competent to restart viral replication when treatment is interrupted. Hence, this replication-competent provirus is the cause of viral rebound and is called the viral reservoir. The exact site of proviral integration within the host's cellular chromosome may affect the transcriptional activity of HIV. Thanks to recent technological advances, HIV-1 integration site analysis has been used to assess HIV-1 reservoirs in HIV-infected individuals. Analysis of HIV-1 integration sites in infected individuals undergoing suppressive ART led to identification of expanded clonal cell populations, indicating that clonal proliferation of the proviral reservoir may contribute to the long-term persistence of viral reservoirs. Here we describe the findings of several clinical studies, where a comprehensive HIV-1 integration site analysis was performed.